Comparison of joint position sense measured by inertial sensors embedded in portable digital devices with different masses - Almeida, José Ramon Gama; Monteiro, Luis Carlos Pereira; de Souza, Pedro Henrique Castro; dos Santos Cabral, André; Belgamo, Anderson; de Athayde Costa e Silva, Anselmo; Crisp, Alex; Callegari, Bianca; Brito, Aymee Lobato; Santos Ávila, Paulo Eduardo; da Silva, José Aparecido; de Nazareth Bastos, Gilmara; et al. (Frontiers in Neuroscience, 2025)
BackgroundJoint position sense can be assessed using various devices, including inertial sensors embedded in smartphones and wearable technologies. However, the mass of these portable instruments may influence proprioceptive input during joint repositioning tasks.PurposeThis study aimed to compare participants’ performance in a joint position sense task using a smartphone and an ultra-light wearable sensor to measure elbow angular displacement.MethodsSixteen adults participated in a passive-active joint position sense test. In this task, participants were required to memorize a passively flexed elbow position and actively reposition the joint across four trials. The angular position during joint repositioning, as well as absolute and relative errors, were compared between trials using a smartphone (weighing several hundred grams) and an ultra-light wearable sensor (weighing only a few dozen grams). Agreement analysis between the devices and reliability assessments for inter-device measurements and for each device were conducted.ResultsNo significant variation in the joint angle at the target position was observed across trials using the ultra-light wearable sensor. In contrast, a significant increase in joint angle at the target position was noted when the smartphone was used. Absolute errors were similar between devices, while relative errors showed significant differences in the first two trials. Overall, systematic biases favored the measurements obtained with the smartphone and inter-device reliability were moderate. Smartphone demonstrated moderate-to-good reliability, and the wearable had poor-to-moderate in test–retest evaluation.ConclusionAlthough measurements from the two devices showed agreement, significant systematic biases were observed, favoring the heavier device. Both the smartphone and the wearable sensor provided reliable measurements for assessing elbow joint position sense.